Improved hospital discharge and cost savings with esophageal cooling during left atrial ablation. (31st December 2023) - Joseph, Christopher; Cooper, Julie; Sikka, Rishi; Zagrodzky, Jason; Turer, Robert W.; McDonald, Samuel A.; Kulstad, Erik; Daniels, James
Abstract: Background: Left atrial ablation to obtain pulmonary vein isolation (PVI) for the treatment of atrial fibrillation (AF) is a technologically intensive procedure utilizing innovative and continually improving technology. Changes in the technology utilized for PVI can in turn lead to changes in procedure costs. Because of the proximity of the esophagus to the posterior wall of the left atrium, various technologies have been utilized to protect against thermal injury during ablation. The impact on hospital costs during PVI ablation from utilization of different technologies for esophageal protection during ablation has not previously been evaluated. Objective: To compare the costs of active esophageal cooling to luminal esophageal temperature (LET) monitoring during left atrial ablation. Methods: We performed a time-driven activity-based costing (TDABC) analysis to determine costs for PVI procedures. Published data and literature review were utilized to determine differences in procedure time and same-day discharge rates using different esophageal protection technologies and to determine the cost impacts of same-day discharge versus overnight hospitalization after PVI procedures. The total costs were then compared between cases using active esophageal cooling to those using LET monitoring. Results: The effect of implementing active esophageal cooling was associated with up to a 24.7% reduction in mean total procedure time, and an 18% increase in same-day discharge rate. TDABC analysis identified a 681 reduction in procedure costs associated with the use of active esophageal cooling after including the cost of the esophageal cooling device. Factoring in the 18% increase in same-day discharge resulted in an increased cost savings of 2, 135 per procedure. Conclusions: The use of active esophageal cooling is associated with significant cost-savings when compared to traditional LET monitoring, even after accounting for the additional cost of the cooling device. These savings originate from a per-patient procedural time savings and a per-population improvement in same-day discharge rate.